The European Economic Crisis in a Global Context and its Originator - Kallianiotis, Ioannis N. (Archives of Business Research, 2015)
In this paper, the European economic crisis is discussed by examining chronologically the events that started in the U.S. (the originator) in August 2007 and due to globalization they continued in the highly indebted Euro-zone members. The common public policy and the common currency in Euro-area do not help the member-nations to improve their economies and overcome the recession because these countries are different and need each one its own policy and target interest rate. There were too many mistakes that led us to the latest financial crisis and authorities have to prevent these crises. The enormous debts in the U.S. and in the EU member-nations are unsustainable and new mixed public policies and regulations are needed to avoid similar negative effects in the future. Austerities and contractionary policies, during periods of recession (with negative growth of the real GDP and extremely high unemployment), are exactly the opposite of what the economies want and these anti-social policies are very suspicious for any thinking person. We have to go back to a value oriented socio-economic system, where humans will be in its center and core.